UNA NUEVA ESPECIE DE SPINOLIELLA (APOIDEA: ANDRENIDAE) DEL NORTE DE CHILE - Toro, Haroldo (Acta Entomológica Chilena, 2022)
Spinoliella (Spinoliella) longirostris n. sp . (Andrenidae: Panurginae), from then or th part of Chile is described . This species is easily recognized for the long gloss a and its long projected clypeus.